Incidence, spatial distribution and damage severity by the sweet potato weevils in sweet potato producing areas of Central Tanzania - P. Mkuki, Lucas; M. Rwegasira, Gration (Journal of Pure and Applied Agriculture, 2023)
Sweet potato (Ipomoea batatas (L.) Lam) is an important staple food and commercial crop in central Tanzania and most of the tropical countries. The on-farm crop productivity in the country is low estimated at 9.5 t ha-1 . Of this, the proportion of marketable yield is even lower due to substantial damages inflicted by the sweet potato weevils, the Cylas spp. A study was conducted to establish the pest status and distribution of weevils in Gairo and Ikungi districts of central Tanzania.